(untitled) (Mustansiria Dental Journal, 2018)
Partial recording of indices of periodontitis have long been used in clinical and epidemiological studies to predict full-mouth situation. The two most widely used partial recording indices for periodontal surveys are the community periodontal index of treatment needs (CPITN) and the Ramfjord teeth. The aim of this study was to evaluate the usefulness of Ramfjord teeth in predicting the full-mouth periodontal status of an adult population in patient attending the collage of dentistry- Baghdad University. The study participants were 240 patients we divide them into three main groups according to the age of the patients and each group were divided in to two sub groups according to the sex of the patients. Pocket depth was measured in millimeters with periodontal probe The difference in the mean pocket depth measured from the full mouth(F) and Ramfjord teeth(R) by using paired t - test was non significant in all the groups. Also in all groups the correlation coefficient as well as beta coefficient was high The high agreement between Ramfjord teeth and full mouth periodontal pocket depth confirm the epidemiological validity of Ramfjord teeth to represent the full mouth.